Case Report: Cerebral Venous Sinus Thrombosis and COVID-19 Infection - Anipindi, Manasa; Scott, Amanda; Joyce, Li; Wali, Salman; Morginstin, Mark (Frontiers in Medicine, 2021)
COVID-19 is caused by SARS-CoV-2 virus. COVID-19 was declared a pandemic in March 2020 and has changed our lives in many ways. This infection induces a hypercoagulable state leading to arterial and venous thrombosis. The exact pathophysiology of thrombosis is unknown; however, various theories have been postulated including excessive cytokine release, endothelial activation, and disseminated intravascular coagulation (DIC). We present a patient diagnosed with cerebral venous sinus thrombosis (CVST) with COVID-19 infection. A 66-year-old man presented to hospital for evaluation of persistent headaches. He tested positive for COVID-19, magnetic resonance imaging of the brain and computed tomography venogram revealed CVST. He was started on heparin drip in the hospital and transitioned to oral anticoagulants at the time of discharge. His headaches improved with treatment. Even though headache is the most frequent and initial symptom of cerebral venous thrombosis it is rarely the only symptom. A high index of suspicion is therefore required to diagnose CVST especially if the patient presents with a simple complaint like headache. Common complaints can delay the diagnosis leading to disease progression. Considering the high mortality rates in patients diagnosed with CVST, we suggest the importance of knowing the association between COVID-19 infection and CVST especially in susceptible patients.